The community mental health team fidelity scale: A measure of program fidelity of social networks interventions for severe mental illness - Alvarez-Monjaras, Mauricio; Lotmore, Melissa; Razzaque, Russell; Hopfenbeck, Mark Steven; Pilling, Stephen (Frontiers in Psychology, 2023)
Open dialogue (OD) is a multi-component therapeutic and organizational intervention for crisis and continuing community mental health care with a therapeutic focus on clients’ social networks. The development and implementation of this model of care in the United Kingdom requires considerable contextual adaptations which need to be assessed to support effective implementation. Program fidelity–the extent to which core components of an intervention are delivered as intended by an intervention protocol at all levels–is crucial for these adaptations. Aims To develop, pilot, and implement a program fidelity measure for community mental health services providing OD and ‘treatment as usual’ (TAU) or standard NHS crisis and community care. Methods Measure structure, content, and scoring were developed and refined through an iterative process of discussion between the research team and OD experts. Measure was piloted in the 6 OD and 6 TAU services participating in a large-scale research program. Results Initial data suggests that the Community Mental Health Team Fidelity Scale (COM-FIDE) is a potentially reliable and feasible measure of the fidelity of community mental health services and specific OD components of such services.